Study on the calibration method for tri-axis fluxgate gradiometer. Issue 5 (February 2020) - Xu, Chaoqun; Huang, Kui; Zhang, Shaohua; Meng, Lifei
Abstract: Aiming at the measurement errors caused by non-orthogonality, inconsistent sensitivity, zero-offset of the tri-axis fluxgate sensor and the position misalignment of two fluxgate sensors composed of the gradiometer, this paper establishes the correction model of measurement error of magnetometer and gradiometer, puts forward the comprehensive coefficient method, and uses the non-magnetic turntable to calibrate the Mag648 three-axis magnetometer and gradiometer in the uniform magnetic environment. The experimental results show that the method can reduce the maximum total magnetic field deviation of the two magnetometers from 552.4 nT to 15.0 nT, and reduce the maximum output deviation of the three-component gradiometer from 3891.5 nT to 37.2 nT, which effectively improves the reliability of the three-axis magnetic sensor in measurement.